Remittances and the brain drain: Evidence from microdata for Sub-Saharan Africa - Julia Bredtmann; Fernanda Martínez Flores; Sebastian Otten (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
Research on the relationship between high-skilled migration and remittances has been limited by the lack of suitable microdata. We create a unique cross-country dataset by combining household surveys from five Sub-Saharan African countries that enables us to analyze the effect of migrants' education on their remittance behavior. Having comprehensive information on both ends of the migrant-origin household relationship and employing household fixed effects specifications that only use within-household variation for identification allows us to address the problem of unobserved heterogeneity across migrants' origin households. Our results reveal that migrants' education has no significant impact on the likelihood of sending remittances. Conditional on sending remittances, however, high-skilled migrants send significantly higher amounts of money to their households left behind. This effect holds for the sub-groups of internal migrants and migrants in non-OECD countries, while it vanishes for migrants in OECD destination countries once characteristics of the origin household are controlled for. – – Auf Basis von Haushaltsbefragungen in fünf Ländern Sub-Sahara Afrikas untersuchen wir den Einfluss der Bildung von Migranten auf deren Rücküberweisungen an ihre im Heimatland verbliebenen Haushalte. Das Vorhandensein umfangreicher Informationen über die Migranten als auch über die Haushalte im Heimatland sowie die Verwendung von Haushalts-Fixed-Effects-Schätzungen erlauben es uns, das Problem unbeobachtbarer Heterogenität zwischen den Herkunftshaushalten zu adressieren. Unsere Ergebnisse zeigen, dass die Bildung der Migranten keinen signifikanten Einfluss auf deren Wahrscheinlichkeit hat, Rücküberweisungen zu schicken. Gegeben, dass Rücküberweisungen gesendet werden, überweisen Migranten mit einem Universitätsabschluss jedoch signifikant höhere Beträge an ihre Herkunftshaushalte als geringer qualifizierte Migranten. Schätzungen für unterschiedliche Gruppen von Migranten zeigen, dass dieser Effekt für interne Migranten sowie für Migranten in Nicht-OECD-Ländern bestehen bleibt. Für Migranten in OECD-Ländern finden wir hingegen keinen signifikanten Einfluss des Bildungsniveaus auf deren Rücküberweisungen sobald Charakteristika des Haushaltes im Herkunftsland in den Modellen berücksichtigt werden.
Keywords: F22; F24; O15; 330; migration; remittances; skill level; brain drain; Sub-Saharan Africa